Комплексний аналіз ризику банкрутства корпорацій в умовах невизначеності. Частина 1 - Zgurovsky, M. Z.; Zaychenko, Yu. P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
Different models and methods of enterprises’ bankruptcy risk analysis are considered. The method of Discriminant analysis of E.Altman and fuzzy-multiple method of bankruptcy risk analysis of Nedosekin are considered. The experimental investigations of the clear and fuzzy methods of bankruptcy risk analysis, which are considered on the example of the Ukrainian enterprises, are carried out; their efficiency is estimated and the most adequate method is determined.